Does the Secondary Loan Market Reduce Borrowing Costs? - Kamstra, Mark J.; Roberts, Gordon S.; Shao, Pei (Review of Finance, 2014)
Abstract We show that lenders make price concessions for the right to resell loans and reveal a strong countervailing association between the ex ante probability of loan resale and the initial loan spreads. We disentangle the side effects (reduced monitoring) from the benefits (enhanced liquidity) brought by the secondary loan resales. The average net impact of simultaneously reducing the probability of the presence of resale constraint and raising the probability of resale across the full sample is to lower spreads by 14 basis points. On balance, the secondary loan market provides clear benefits to the issuers of debt.